Cost estimation relationships of a small scale linear Fresnel reflector. (April 2019) - Barbón, A.; Sánchez-Rodríguez, J.A.; Bayón, L.; Bayón-Cueli, C.
Abstract: This paper presents a cost estimating relationship ( C E R ) of a novel small scale linear Fresnel reflector ( S S L F R ). The C E R has been developed analyzing in detail the manufacturing processes of the S S L F R, its parameters, and the possible sub-components. As a result of this analysis, the SSLFR has been divided into 8 sub-components: fixed and mobile structures, movement units, mirror units, secondary reflector system, tracking system, assembly, and foundation. These sub-components are described in detail and designed using Autodesk Inventor, specifying manufacturing materials and processes. The study includes a full stress analysis of the sub-components, considering self weight, snow loads, and wind loads. For each sub-component an estimate of the primary costs is presented and also a relationship between the cost and the geometric parameters of the S S L F R . The primary costs considered include material, labor, and tooling costs. A numerical example shows the suitability of the proposed approach. Highlights: We study an accurate cost model of a small scale linear Fresnel reflector (SSLFR). The relationships between the parameters and costs are analyzed. Total cost is significantly impacted by number of mirrors. This study can be used in the optimization of SSLFRs.